Leaf morphology in cowpea [Vigna unguiculata (L.) Walp]: QTL analysis, physical mapping and identifying a candidate gene using synteny with model legume species - Pottorff, M.; Ehlers, J.D.; Fatokun, C.A.; Roberts, P.A.; Close, T.J. (Springer, 2012)
Cowpea [Vigna unguiculata (L.) Walp] exhibits a considerable variation in leaf shape. Although cowpea is mostly utilized as a dry grain and animal fodder crop, cowpea leaves are also used as a high-protein pot herb in many countries of Africa.